2002
DOI: 10.1385/bter:85:1:01
|View full text |Cite
|
Sign up to set email alerts
|

Measurements in Potassium-Supplemented Athletes During and After Hypokinetic and Ambulatory Conditions

Abstract: Hypokinesia (diminished movement) induces significant potassium (K) changes; however, little is known about K deposition and deficiency during hypokinesia (HK). Using K supplements during and after HK, the aim was to establish body K deposition and K deficiency during HK. Studies were done during the pre-HK period of 30 d, HK period of 364 d, and post-HK period of 30 d. Forty male trained athletes aged 24.9 +/- 8.0 y were chosen as subjects. They were equally divided into four groups: unsupplemented active con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…During a normal muscular activity, K + depletion develops because of the decreased K + consumption, excessive K + losses through gastrointestinal tract and kidney, and a redistribution of K + within the body due to insulin intake, and magnesium depletion. However, K + depletion during prolonged HK is much more complicated, because K + depletion is present with and without K + supplementation, and K + depletion is accompanied by a significant increase of plasma K + level [5][6][7][8][9] and K + losses [5][6][7][8][9]. Using K + supplementation to normalize K + depletion during prolonged HK had shown that K + is neither entering nor being retained by muscles, where most K + is normally deposited.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…During a normal muscular activity, K + depletion develops because of the decreased K + consumption, excessive K + losses through gastrointestinal tract and kidney, and a redistribution of K + within the body due to insulin intake, and magnesium depletion. However, K + depletion during prolonged HK is much more complicated, because K + depletion is present with and without K + supplementation, and K + depletion is accompanied by a significant increase of plasma K + level [5][6][7][8][9] and K + losses [5][6][7][8][9]. Using K + supplementation to normalize K + depletion during prolonged HK had shown that K + is neither entering nor being retained by muscles, where most K + is normally deposited.…”
Section: Introductionmentioning
confidence: 99%
“…Using K + supplementation to normalize K + depletion during prolonged HK had shown that K + is neither entering nor being retained by muscles, where most K + is normally deposited. This shows the presence of another mechanisms and primarily the presence of decreased K + deposition, that may lead to significant increase of K + losses with K + imbalance and consequently may contribute to the development of K + depletion in healthy subjects during prolonged HK [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations